(untitled) (Journal of Foreign Language Studies, 2024)
At the Department of Japanese - Hanoi University, improving teaching materials to develop standard textbooks for teaching Japanese Linguistics I, a required subject of the bachelor program in Japanese Studies, is one of the current missions. In this paper, with the results of the survey and analysis based on the subject’s syllabus and the opinions of learners and teachers, we propose some appropriate and effective improvements in the teaching materials of Japanese Linguistics subject.